Dietary nitrate and population health: a narrative review of the translational potential of existing laboratory studies - Oliver M. Shannon; Chris Easton; Anthony I. Shepherd; Mario Siervo; Stephen J. Bailey; Tom Clifford (BMC, 2021)
Abstract Background Dietary inorganic nitrate (NO3 −) is a polyatomic ion, which is present in large quantities in green leafy vegetables and beetroot, and has attracted considerable attention in recent years as a potential health-promoting dietary compound. Numerous small, well-controlled laboratory studies have reported beneficial health effects of inorganic NO3 − consumption on blood pressure, endothelial function, cerebrovascular blood flow, cognitive function, and exercise performance. Translating the findings from small laboratory studies into 'real-world' applications requires careful consideration. Main body This article provides a brief overview of the existing empirical evidence basis for the purported health-promoting effects of dietary NO3 − consumption. Key areas for future research are then proposed to evaluate whether promising findings observed in small animal and human laboratory studies can effectively translate into clinically relevant improvements in population health. These proposals include: 1) conducting large-scale, longer duration trials with hard clinical endpoints (e.g. cardiovascular disease incidence); 2) exploring the feasibility and acceptability of different strategies to facilitate a prolonged increase in dietary NO3 − intake; 3) exploitation of existing cohort studies to explore associations between NO3 − intake and health outcomes, a research approach allowing larger samples sizes and longer duration follow up than is feasible in randomised controlled trials; 4) identifying factors which might account for individual differences in the response to inorganic NO3 − (e.g. sex, genetics, habitual diet) and could assist with targeted/personalised nutritional interventions; 5) exploring the influence of oral health and medication on the therapeutic potential of NO3 − supplementation; and 6) examining potential risk of adverse events with long term high- NO3 − diets. Conclusion The salutary effects of dietary NO3 − are well established in small, well-controlled laboratory studies. Much less is known about the feasibility and efficacy of long-term dietary NO3 − enrichment for promoting health, and the factors which might explain the variable responsiveness to dietary NO3 − supplementation between individuals. Future research focussing on the translation of laboratory data will provide valuable insight into the potential applications of dietary NO3 − supplementation to improve population health.